Association of arterial properties with left ventricular morphology and function in the community. Issue 12 (18th December 2022) - Mukai, Yasuhiro; Nakanishi, Koki; Daimon, Masao; Sawada, Naoko; Hirose, Kazutoshi; Iwama, Kentaro; Yamamoto, Yuko; Yoshida, Yuriko; Ishiwata, Jumpei; Koyama, Katsuhiro; Nakao, Tomoko; Morita, Hiroyuki; et al.
Abstract : Objectives: Arterial structural and functional remodeling is recognized as a key determinant of incident heart failure, although the contribution of arterial properties on left ventricular (LV) remodeling is not fully studied. Aortic dilatation is an early manifestation of arterial remodeling and estimated pulse wave velocity (ePWV) is emerging as a simple measure of arterial stiffness. This study aimed to characterize the association of aortic size and ePWV with LV morphology and function. Methods: The study cohort consisted of 539 participants without overt cardiac disease who underwent extensive cardiovascular examination. Aortic root diameter was measured by two-dimensional echocardiography and ePWV was calculated from a regression equation using age and mean blood pressure. LV global longitudinal strain (LVGLS) was obtained by speckle-tracking echocardiography. Results: Aortic root diameter and ePWV were correlated with LV mass index and LVGLS, while only ePWV was related to E / e′ ratio. In multivariable analysis, aortic root diameter and ePWV were significantly related to LV mass index and LVGLS (all P  < 0.05), and the association of aortic root size and ePWV with LVGLS was independent of LV mass index and E / e′ ratio. Individuals with both aortic root enlargement and increased ePWV had significantly larger LV mass index and reduced LVGLS compared with those either or those with normal aortic size and ePWV (both P  < 0.05). Conclusion: Aortic root size and ePWV were independently associated with unfavorable LV remodeling in individuals free of cardiac disease, which might provide useful information into the pathogenesis-linking arterial remodeling and heart failure.